PENGARUH MOTIVASI KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN KSPPS BAYTUL IKHTIAR DI KOTA BOGOR - Fajar Dwi Saputra; Bonar Frans Sihite (Journal of Research and Publication Innovation, 2025)
This research aims to determine the influence of work motivation and organizational culture on the performance of KSPPS Baytul Ikhtiar employees in Bogor City partially and simultaneously. The research method used is a quantitative method, using questionnaire data collection techniques, primary and secondary data using non-probability sampling techniques with saturated sampling techniques. The results of this research were that all questionnaire items were declared valid by obtaining a calculated r value > r table (0.227) and a reliable level for the Work Motivation variable (X1) 0.945, Organizational Culture (X2) 0.878, Employee Performance (Y) 0.931 which has a Cronbatch Alpha value greater than 0.600. And the results of this research show that work motivation has a significant positive effect on employee performance with the regression equation Y = 17.512 + 0.656 (X1), the correlation coefficient value is 0.734, meaning that the two variables have a strong relationship with a determination coefficient of 53.9% and hypothesis testing is obtained. t count > t table (9,240> 1,666). Organizational culture has a significant positive effect on employee performance with the regression equation Y = 23.694 + 0.419 (X2), the correlation coefficient value is 0.464, meaning that the two variables have a moderate relationship with a coefficient of determination of 21.5% and the hypothesis test is obtained t count > t table (4,470>1,666). Work Motivation and Organizational Culture have a positive and significant effect on Employee Performance with the regression equation Y = 16.160+0.530(X1) + 0.075(X2), the correlation coefficient value is 0.544, meaning that the independent variable and the dependent variable have a moderate level of relationship with a coefficient of determination of 54 .4% while the remaining 45.6% is influenced by other factors. Hypothesis testing obtained F count > F table or (42.916> 3.120) thus H03 was rejected and Ha3 was accepted, this shows that there is a significant simultaneous influence between Work Motivation and Organizational Culture on the Performance of KSPPS Baytul Ikhtiar Employees in Bogor City.